Research for Development and Validation of Honesty Behavior of Youths and Measurement Invariance (International Journal of Psychosocial Rehabilitation, 2020)
Honesty to oneself, surrounding people, communities and societies is the fundamental of expression of social morality of youths in the community to grow and become a smart, decent and happy citizen in the future. This research aimed 1) to analyze exploratory factor of the honesty behavior, 2) to analyze the second-order confirmatory factor of honesty behavior and 3) to examine measurement invariance of the honesty behavior. The research samples were selected with multistage quota random sampling method which included 2 groups of youths in the communities: 1) the sample cluster for exploratory factory analysis totaling 300 people and 2) the sample cluster for second order confirmatory factor analysis. After that, 300 samples were studied for measurement invariance o. The analysis result could be summarized into 3 issues as follows. First, when analyzing the exploratory components of honesty measurement form, the researcher found that there were 4 components of the measurement model including 1) self-dishonesty for 5 items, 2) corruption in studying for 3 items,3) action for personal benefits for 4 items and 4) honesty to other persons for 3 items, totaling 15 items. These could be used to explain variance for 65.68%. Second, when analyzed, the second order confirmatory factor showed that the model was in harmony with empirical data with Chi-Square = 115.83 df = 69, Chi-Square/df = 1.68, RMSEA=0.04, NFI=0.98, GFI = 0.98, CFI = 0.99, and AGFI= 0.91. Third, the analysis of model invariance indicated that 1) no form invariance was found and 2) no factorial invariance existed in the community where the youths stayed.